Gambaran Pengetahuan Ibu Tentang Pijat Bayi Di Desa Dajan Peken Tabanan - Cokorda Istri Mita Pemayun; Rini Winangsih (STIKES ADVAITA MEDIKA TABANAN, 2021)
Abstract - is the oldest and most popular touch therapy. Lack of stimulation given to babies adds to the delay in baby development. This baby massage needs to be known by a mother because with the touch and eyes when the massage will be able to drain the strength of the relationship between the two. The purpose of this study is to describe the knowledge of mothers about infant massage in the village of Dajan Peken Tabanan. The research methodology used a quantitative descriptive method which was carried out in the village of Dajan Peken Tabanan in September 2020. The sample in this study were 33 mothers who had babies aged 0-12 months and were taken by total sampling. The instrument in this study used a questionnaire sheet. The data analysis technique used univariate analysis. The result of the research is that the knowledge of mothers about baby massage in the village of Dajan Peken Tabanan is mostly in the sufficient category, namely as many as 22 people (66.7%). The conclusion in this study is that the description of the knowledge of mothers about baby massage in the village of Dajan Peken Tabanan is mostly sufficient as many as 22 respondents (66.7%). Therefore, Posyandu cadres together with midwives should provide information or counseling about infant massage to mothers who have babies 0-12 months.